2018
DOI: 10.13057/biodiv/d190425
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of urinary tract infection bacteria in children in Indonesia based on metagenomic approach

Abstract: Christine G, Budiarti S, Astuti RI. 2018. Diversity of urinary tract infection bacteria in children in Indonesia based onmetagenomic approach. Biodiversitas 19: 1375-1381. Urinary tract infection (UTI) is a common bacterial infection in childhood in bothmales and females. The infection is usually caused by bacterial invasion of the urinary tract including the lower and the upper urinarytract. In Indonesia, to the best our knowledge, the diversity of urinary tract infection bacteria has not been reported yet. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
(19 reference statements)
0
4
0
Order By: Relevance
“…Citrobacter braakii used in this study was obtained from the urine of UTI-diagnosed children, which has been isolated from our earlier study (Christine et al 2018). Bacterial isolate was routinely culture in Luria Bertani agar (LA) medium.…”
Section: Bacterial Isolate Source and Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Citrobacter braakii used in this study was obtained from the urine of UTI-diagnosed children, which has been isolated from our earlier study (Christine et al 2018). Bacterial isolate was routinely culture in Luria Bertani agar (LA) medium.…”
Section: Bacterial Isolate Source and Sample Collectionmentioning
confidence: 99%
“…Citrobacter strains are the third most common bacteria causing UTI in hospitalized patients besides Escherichia coli and Klebsiella strains up to 9.4% of all bacterial isolates obtained (Metri et al 2013). A previous study through a culture-based approach also revealed that C. braakii has been found in urine from UTI-diagnosed children (Christine et al 2018). Therefore, it is an emergence to find an effective treatment strategy to control the infection cases caused by this bacterium.…”
Section: Introductionmentioning
confidence: 99%
“…It means that this bacteria group is still potential to be used as a source of novel antibacterial compound for some infectious diseases. Christine et al (2018) reported that Escherichia coli, Acinetobacter calcoaceticus, Citrobacter braakii, and Klebsiella pneumoniae were found in UTI urine patients. In accordance with the requirement of new antibacterial compounds and the existence of actinomycetes in rhizosphere, this research conducted some methods to find novel antibacterial compounds from actinomycetes for bacteria from UTI patients as a target.…”
Section: Introductionmentioning
confidence: 99%
“…Some urine samples from different childhood's patient in Indonesia also showed the presence of culturable UPEC and unculturable Escherichia sp. based on 16S rRNA gene (Christine et al 2018). Mechanism of UPEC in infecting urinary tract is commonly initiated by colonizing E. coli from anus to periurethral slot, then it moves to bladder and kidney by ascending.…”
Section: Introductionmentioning
confidence: 99%